Analysis of Service Quality at the Truntum Padang Hotel - Zengg, Zengg; Husna, Rifdatul; Riesa, Rafidola Mareta; Derizal, Derizal (ABEC Indonesia, 2024)
This research aims to analyze the quality of service at the Truntum Padang Hotel, based on room occupancydata from November 2022 to February 2023. The room occupancy rate at the Truntum Padang Hotel has decreased, evenin January it did not reach 50%. From February to April 2023, the Truntum Padang Hotel's room occupancy rate is unstableand still has not reached 90% according to management's target. Even though the Truntum Padang Hotel is the only hotelmanaged by a State-Owned Enterprise (BUMN) in Padang City. The main objective analysis in this research is to look atthe quality of service at the Truntum Padang Hotel. This type of research is a quantitative descriptive research type of datasource used for both primary and secondary data. Purposive sampling was used as a sampling technique in this research,with a total sample of 100 respondents. Based on the results of a questionnaire using a Likert scale, it shows that the analysisof service quality at the Truntum Padang Hotel, seen from service quality indicators, has a percentage of 52%, namely atthe interval limit of 3, 26-4.00 in the satisfied category.